IMPACT OF WEATHER PARAMETERS ON THE INCIDENCE OF WHITEFLY POPULATION IN DIFFERENT POTATO (Solanum tuberosum L.) CULTIVARS - B. KAHAR*; P. MONDAL (The Journal of Research ANGRAU, 2020)
Potato cultivars (13 no.) were assessed for the incidence of whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) during Rabi seasons from 2015-2016 to 2017-2018. Initial whitefly population is observed in the crop during3rd week of December (51st to 52nd meteorological standard week) with the peak at 3rd to 4th week of February (7th to 8th MSW). However, the level of whitefly population was varied among the potato cultivars. In all the cultivars, the whitefly population declined gradually after the peak, however, over the duration the attainment of a higher population differed among the cultivars. A significant and positive correlation of whitefly population was recorded with maximum and minimum temperature and bright sunshine hours, whereas, maximum and minimum relative humidity had a negative correlation. It was evident from the step-wise multiple regression analysis that maximum temperature had a significant influence on the fluctuation of whitefly population. Besides, collective influence (41.1% to 66.5%) of all the weather parameters on the whitefly population was also recorded (from adjusted R2 value 0.411 to 0.665) in different potatocultivars.